PENGARUH MEKANISME CORPORATE GOVERNANCE TERHADAP KUALITAS PELAPORAN KEUANGAN PADA PERUSAHAAN NON KEUANGAN TERDAFTAR DI BEI - iswara, ulfah setia (JURNAL EKONOMI AKUNTANSI DAN MANAJEMEN, 2016)
ABSTRACT Financial reporting is important for interested parties because it includes financial information and other specific information that may influence decision- making. Efforts in presenting quality financial reporting to be a challenge for companies because of the increasing number of cases of manipulation of financial statements. Corporate governance mechanism has an important role to support the achievement of financial reporting quality. The purpose of this study was to examine and obtain empirical evidence of the influence of corporate governance mechanisms on the quality of financial reporting. This research is quantitative. The sample used in this study is a non- financial companies listed on the Indonesia Stock Exchange during the period from 2009 until 2013 amounted to 660 companies. Analysis of the data used in this study is multiple regression analysis. The results showed that the proportion of independent board, managerial ownership and institutional ownership has proved a significant effect on the quality of financial reporting. Age of the company, type of industry, quality audit, leverage, liquidity and growth as control variables proved to have a significant effect on the quality of financial reporting. Â  Keywords: corporate governance, the proportion of independent board, managerial ownership, institutional ownership, the quality of financial reporting